On some Vetigastropoda (Mollusca, Gastropoda) from the Plio-Pleistocene of the Philippines with descriptions of three new species - Helwerda, Renate Ariane; Wesselingh, Frank Pieter; Williams, Suzanne T. (Zootaxa, 2014)
We studied representatives of seven vetigastropod families in an extremely well-preserved Plio-Pleistocene mollusc fauna found in relatively deep water sediments (c. 200–300 m paleodepth) from the north-western Philippines. The fauna is systematically described and its paleoenvironmental and paleobiogeographical character is explored. Twenty-six species of gastropods were studied, three of which are described as new: Halystina conoidea n. sp., Calliotropis arenosa n. sp. and Ethminolia wareni n. sp. Four new combinations are proposed: Pseudotalopia taiwanensis (Chen, 2006), Solariella segersi (Poppe, Tagaro & Dekker, 2006), Zetela tabakotanii (Poppe, Tagaro & Dekker, 2006) and Ilanga konos (Vilvens, 2009). Fourteen species are known living. Most extant species nowadays occur around the Philippines. Two of the species also occur in Neogene deposits from western Pacific islands. The new fauna offers insights into the character of relatively deep water Indo-West Pacific mollusc faunas prior to the onset of the late Quaternary ice ages.